Transformasi Media Pembelajaran Sebagai Upaya Optimalisasi Perkuliahan Agama Hindu Pada Mata Kuliah Inti Prodi Penerangan Agama Hindu STAH Negeri Mpu Kuturan Singaraja - Gede Agus Jaya Negara; I Nyoman Ariyoga; I Nyoman Buda Asmara Putra (Jurnal Penelitian Agama Hindu, 2022)
The Hindu Religious Information Study Program, STAHN Mpu Kuturan Singaraja, is committed to producing Hindu religious instructors who have competencies according to the profile of graduates. The process of supporting the existence of the Hindu Religious Information Study Program requires optimization of core courses, one of which is Hinduism by carrying out a transformation of learning media, especially during the Covid-19 pandemic. The purpose of this study was to identify the transformation of learning media, to know the process of transforming learning media, and to identify the impact of the transformation of learning media to the core courses of Hindu Religious Information Study Program. This type of research is qualitative research, namely research that produces descriptive data in the form of words. Through analysis based on the theory of behaviorism and the theory of social change, Technological Determinism. The results of this study are preparing supporting facilities, participating in training, exchanging information and knowledge, and social media-based assignments. To support these efforts, the learning media transformation process includes: the selection of learning media and the implementation of distance learning media transformation in the Hindu Religious Information Study Program. The implication is that by increasing digital literacy, gaining ease in accessing information, being flexible, efficient and of good quality), the results of the research conclude that students are skilled in using social media as well as increasing the ability of lecturers and students in using IT, increasing student scores, and STAH Negeri Mpu Kuturan Singaraja institutions is ready in terms of digital transformation for mutual progress.